Analisis Pengelolaan Sarana Dan Prasarana Terhadap Efektivitas Pembelajaran Di Sekolah Dasar - Jose Hape; Adi Winanto (STKIP Subang, 2026)
The management of facilities and infrastructure is a crucial factor in enhancing learning effectiveness in primary schools. The availability and optimal utilization of educational facilities create a comfortable learning environment that supports the achievement of learning objectives. However, challenges persist in this area, such as budget constraints, a lack of technology-based facilities, and suboptimal facility maintenance. This study aims to analyze the management of facilities and infrastructure in supporting learning effectiveness at SD Negeri 15 Ternate City. A descriptive qualitative approach was employed, with the principal, teachers, and educational staff serving as research subjects. Data collection involved observation, structured interviews, and documentation, while data analysis proceeded through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that facility and infrastructure management has been implemented effectively through a school-based management approach involving the entire school community. The utilization of classrooms, the library, learning media, and the school environment supports the learning process, fostering a comfortable and conducive atmosphere. Nevertheless, certain obstacles remain, including budget limitations, a shortage of management personnel, damage to some facilities, and a scarcity of technology-based learning media. The school’s efforts to address these issues include optimizing the use of existing facilities, fostering collaboration among the school community, and continuously improving management practices. Thus, effective management of facilities and infrastructure contributes positively to enhancing learning effectiveness and the quality of education in primary schools.